Pengaruh Karakteristik Kepribadian Enterpreneur terhadap Intensi Berwirausaha pada Mahasiswa Universitas Muhammadiyah Prof DR Hamka - Alvin Eryandra (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Entrepreneurship research is gaining attention in most developing countries as an attempt to break out of poverty for their people. It cannot be denied that entrepreneurship as a concept is a practical approach that can achieve sustainable economic development which has become the goal of most developing countries. This study was conducted with the aim to determine the effect of entrepreneurial personality characteristics on entrepreneurial intention in Uhamka students. This study will adopt a measuring instrument from Anwar & Saleem (2019) which consists of 38 items to measure risk taking, innovativeness, locus of control, need for achievement, self-efficacy and tolerance of ambiguity. The entrepreneurial intention variable is measured using the Entrepreneurial Intention scale from Wang (2016) which consists of 9 question items. This scale has two dimensions, namely the belief dimension and the preparation dimension. The Entrepreneurial Intention measuring instrument is used to see students' attitudes towards entrepreneurial career commitment and the preparation process to become an entrepreneur. The reliability of the belief dimension is 0.912 and the preparation dimension is 0.807. The research respondents were 331 students from various faculties at Uhamka who had completed entrepreneurship courses. The results of statistical analysis show that there is a significant influence between entrepreneurial personality characteristics on entrepreneurial intention